A coordenação de curso de licenciatura em matemática: dimensões da função no contexto do IFSP - Cruz, Paulo Henrique Correia Araújo da (Universidade Federal de São Carlos, 2023)
Research developed in the Postgraduate Program, Doctorate in Education, at the Federal University of São Carlos, Sorocaba campus (UFSCar-So), addresses the role of Coordination of the Mathematics Teaching degree program in the context of the São Paulo Institute of Education, Science, and Technology (IFSP). It is based on the thesis that the Coordination of the Mathematics Teaching program at IFSP is based on three dimensions, namely, Teaching, Management, and Pedagogical, each with their respective specific knowledge related to the work and educational background of the teacher who holds the position. Given the general objective of identifying and understanding the specific knowledge required for the role, which constitute the structuring dimensions of the Coordination of the Mathematics Teaching program at IFSP, the specific objectives are: i) to understand the influences of the teacher's educational background on the exercise of the Coordination of the Course; ii) to identify and analyze the dimensions of the coordination exercise based on the specific knowledge present in the coordinators' reports. In a qualitative and interpretive approach, we collected data from institutional documents, questionnaires (asynchronous), and roundtable discussions (synchronous) with the coordinating professors who held the position between the years 2008-2021, at the thirteen campuses where the program is offered at IFSP. The questionnaire data were categorized, while the roundtable discussion data were organized into three thematic units, adapting the episodes method. After understanding the influences of the educational background and the establishment of specific knowledge, we initially concluded that there is a need for the teaching professional, in the exercise of the role, to reflect on this knowledge, with reference to the aforementioned three dimensions: Teaching, Management, and Pedagogical. Such interference and action on the exercise of the role and, consequently, on how the initial training of future mathematics teachers takes place reflects the recognition of an institutional commitment to the formation of this professional. In short, assuming the Coordination of a Mathematics Teaching degree program at IFSP implies articulating ideas and people, transforming the culture and climate of the program, exercising leadership in an academic community, based on democratic and participatory management, guiding the training of future mathematics teachers and their educators based on their teaching experience. The proposal of a theoretical model, concluding this work, and systematizing the Course Coordination through the triad of the mentioned dimensions, their respective specific knowledge, and their interrelationships with the professional's educational background, aims to support future discussions on normative instruments and the necessary conditions for the professional practice of this role in other programs/institutions, as well as the means and ways to measure the impact that each dimension has on the role, throughout its practice.
The coordination of a license course in mathematics: dimensions of the function in the context of the IFSP
Keywords: Coordenador de Curso; Licenciatura em Matemática; IFSP; Dimensões da função; Conhecimentos Específicos; Course Coordinator; Degree in Mathematics; Dimensions of function; Specific Knowledge; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL